2021
DOI: 10.1007/s00296-020-04784-1
|View full text |Cite
|
Sign up to set email alerts
|

Topographical analysis of structural lesions between dominant and non-dominant hands in erosive osteoarthritis

Abstract: Objective: This study aims to analyse the preferential topographical distribution of clinical and structural lesions between the dominant and non-dominant hands in erosive hand osteoarthritis (EHOA) patients.Methods: Both hands were assessed via radiography in EHOA patients. A comparative analysis of the clinical features and structural lesions between the dominant and non-dominant hands was performed. The structural lesions were assessed according to the anatomical radiographic score of Verbruggen-Veys (VV). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…In a recent study, Heberden nodes were observed more frequently on the dominant hand. 25 In our study, nodes were more common in the right-hand DIP joints of the third finger.…”
Section: Discussionsupporting
confidence: 47%
“…In a recent study, Heberden nodes were observed more frequently on the dominant hand. 25 In our study, nodes were more common in the right-hand DIP joints of the third finger.…”
Section: Discussionsupporting
confidence: 47%